Identifying degradation patterns of lithium ion batteries from impedance spectroscopy using machine learning - Yunwei Zhang (Nature Portfolio, 2020)
Forecasting the state of health and remaining useful life of batteries is a challenge that limits technologies such as electric vehicles. Here, the authors build an accurate battery performance forecasting system using machine learning.